Accuracy of Modified Checklist for Autism in Toddlers (M-CHAT) in Detecting Autism and Other Developmental Disorders in Community Clinics - Toh, Teck‑Hock; Tan, Vivian Wee-Yen; Lau, Peter Sie-Teck; Andrew, Kiyu (Springer New York LLC., 2017)
This study determined the accuracy of Modified Checklist for Autism in Toddlers (M-CHAT) in detecting toddlers with autism spectrum disorder (ASD) and other developmental disorders (DD) in community mother and child health clinics. We analysed 19,297 eligible toddlers (15–36 months) who had M-CHAT performed in 2006–2011. Overall sensitivities for detecting ASD and all DD were poor but better in the 21 to <27 months and 27–36-month age cohorts (54.5–64.3%). Although positive predictive value (PPV) was poor for ASD, especially the younger cohort, positive M-CHAT helped in detecting all DD (PPV = 81.6%). This suggested M-CHAT for screening ASD was accurate for older cohorts (>21 months) and a useful screening tool for all DD.